Geographical heterogeneity in mountain grasslands dynamics in the Austrian-Italian Tyrol region. (May 2019) - Hinojosa, Leonith; Tasser, Erich; Rüdisser, Johannes; Leitinger, Georg; Schermer, Markus; Lambin, Eric F.; Tappeiner, Ulrike
Abstract: Agricultural land abandonment and transformation of the rural mountain landscapes have been of widespread occurrence in the European mountains. Such changes have strongly affected agricultural land, particularly traditionally used grasslands, which are hotspots of biological and cultural diversity in Alpine countries. We investigated the land use/cover changes and drivers of those changes between 1990 and 2010 in the Austrian and Italian bi-national region of Tyrol. We focus on grasslands as they covered around 94% of the utilized agricultural area since 1990. We mapped changes in grassland areas and assessed the socio-economic and biophysical factors associated with those changes using statistical modelling. Both sub-regions of Tyrol experienced changes in grasslands, but national and local scale factors mediated the impact of regional integration on land use decisions. Marginal grasslands decreased more rapidly in Austria's than in Italy's Tyrol, mostly in high elevation areas. High-management intensity grasslands slightly expanded in Austrian Tyrol, while in Italy's South Tyrol their conversion to other land uses such as permanent crops was more frequent. In the whole Tyrol region, grasslands of high management intensity expanded mostly in municipalities with a larger population, greater livestock density, smaller farms, more remote location, and fewer municipal grasslands and natural parks. Our findings suggest that grasslands conversion is a geographically heterogeneous process. Notwithstanding the de-agrarisation of the Tyrolean landscapes that took place in some Alpine areas, an expansion of grasslands was observed in others. These changes have ecological and social implications. Highlights: The Tyrol shows different patterns of grasslands conversion in Italy and Austria. Socio-economic changes in the 1990–2010 period led to grasslands conversion. Livestock density correlates with expansion of intensively managed grasslands. In Italy's South Tyrol, more grasslands were converted to other land uses.